Orta bilim beriw mekteplerinde qaraqalpaqstan tariyxi páninde oqiwshilarġa tariyxiy bilimlerdi qáliplestiriw usillari hám áhmiyeti - Tleumuratova, N.M (SCIENCE and SOCIETY, 2019)
The article is devoted to the study of the process of formation of schoolchildren’s knowledge in history on the example of the subject "History of Karakalpakstan " and performing these tasks by teachers.
Keywords: history of Karakalpakstan; teaching methods; ways of increasing efficiency of studies